Impact of the sexual abstinence period on the production of seminal reactive oxygen species in patients undergoing intrauterine insemination: A randomized trial. Issue 7 (27th May 2020) - Degirmenci, Yaman; Demirdag, Erhan; Guler, Ismail; Yildiz, Sule; Erdem, Mehmet; Erdem, Ahmet
Abstract: Aim: To evaluate whether the duration of sexual abstinence has impact on oxidative stress in semen samples. Methods: Oxidative reaction was tested for different levels of reactive oxygen species (ROS) by nitro blue tetrazolium assay in 90 patients with the diagnosis of unexplained or male factor infertility that were grouped into 3 groups as 0–2 (group 1), 3–4 (group 2) and >4 days (group 3) of duration of sexual abstinence. Subsequently, the remaining semen was prepared by gradient method for ovarian stimulation and intrauterine insemination (IUI) cycles to compare pregnancy rates in terms of different levels of ROS and different abstinence periods. Results: Increased staining pigment intensity was related to higher level of ROS in >4 days' group as compared to groups 0–2 and 3–4 days (70% vs 43.3% and 50%, P = 0.013 and P = 0.014, respectively). Pregnancy rates significantly decrease with prolonged abstinence period (26.7%, 16.7% and 6.7% in groups 1, 2 and 3, respectively, P = 0.039). Progressive motile sperm count after gradient method of sperm preparation for IUI was highest in 3–4 days of abstinence period than shorter and longer abstinence groups. Conclusion: Longer duration of sexual abstinence causes higher oxidative stress and decreases pregnancy rates in IUI cycles.